When do fractures initiate during the geological history of a sedimentary basin? Test case of a loading-fracturing path methodology. (November 2022) - Petit, Jean-Pierre; Chemenda, Alexandre I.; Minisini, Daniel; Richard, Pascal; Bergman, Steven C.; Gross, Michael
Abstract: We propose a methodology to determine the initiation and reactivation of fracturing during the geological history of a sedimentary basin. The data input is derived from the Eagle Ford unconventional play (Texas, USA) and includes stratigraphy, burial and exhumation, tectonic regimes, regional fractures and faults, in situ stresses, and present-day mechanical properties of rocks. Based on this dataset and mechanical simulations, we build a stress history (the loading path). Using this path and criteria for the tensile and shear failure, we evaluate the temporal intervals when fracturing is possible during the geological history of a sedimentary basin for different scenarios of the associated strength evolution of its material. We conclude that most probably fracturing is initiated in early (shallow) burial conditions, at a post-compaction stage, with no or limited overpressure, when the cohesion of the material is still low. Graphical abstract: Image 1 Highlights: An interdisciplinary methodology is proposed for a geological loading -fracturing path. A loading path is established numerically under geological constraints. Failure conditions are applied to material with increasing strength. Jointing and faulting fracturing windows are defined under minimum overpressure. Fracturing initiates early in incompletely lithified/buried material.